The welfare cost of the EMU for transition countries - Ferreira-Lopes, A. (Prague Economic Papers, 2014)
The Czech Republic, Hungary, and Poland are set to join the European and Monetary Union (EMU) in the near future. This paper offers a framework for the quantitative evaluation of the economic costs of joining the EMU. Using an open economy dynamic general equilibrium model with sticky prices, we investigate the economic implications of the loss of monetary policy flexibility associated with EMU for each of these economies. The main benefit of this general equilibrium approach is that we can directly evaluate the effects of monetary policy in terms of welfare. Our findings suggest that the Czech Republic and Poland may experience sizable welfare costs as a result of joining the EMU. Results for Hungary are less striking as welfare costs in this country seem to be negligible in the benchmark economy. Nevertheless, costs of joining the EMU are higher if government shocks are important and when the trade share with the EMU is small.